Biological features of placental programming. (December 2016) - Thornburg, Kent L.; Kolahi, Kevin; Pierce, Melinda; Valent, Amy; Drake, Rachel; Louey, Samantha
Abstract: The placenta is a key organ in programming the fetus for later disease. This review outlines nine of many structural and physiological features of the placenta which are associated with adult onset chronic disease. 1) Placental efficiency relates the placental mass to the fetal mass. Ratios at the extremes are related to cardiovascular disease risk later in life. 2) Placental shape predicts a large number of disease outcomes in adults but the regulators of placental shape are not known. 3) Non-human primate studies suggest that at about mid-gestation, the placenta becomes less plastic and less able to compensate for pathological stresses. 4) Recent studies suggest that lipids have an important role in regulating placental metabolism and thus the future health of offspring. 5) Placental inflammation affects nutrient transport to the fetus and programs for later disease. 6) Placental insufficiency leads to inadequate fetal growth and elevated risks for later life disease. 7) Maternal height, fat and muscle mass are important in combination with placental size and shape in predicting adult disease. 8) The placenta makes a host of hormones that influence fetal growth and are related to offspring disease. Unfortunately, our knowledge of placental growth and function lags far behind that of other organs. An investment in understanding placental growth and function will yield enormous benefits to human health because it is a key player in the origins of the most expensive and deadly chronic diseases that humans face. Highlights: Many chronic diseases such as coronary heart disease, hypertension, heart failure and sudden cardiac death are related to the growth of the placenta. The ratio of placental weight to birthweight, placental efficiency, predicts a person's risk for ischemic cardiac disease. The shape of the placenta is a strong predictor of cardiovascular diseases and some cancers. The placental production of hormones affects the growth of the fetus which predicts adult-onset disease. One of the great mysteries in placental biology is the transport of lipids.